THE IMPLEMENTATION OF TEACHER COMPETENCY IN CHARACTER BUILDING OF STUDENTS AT SMK NEGERI 1 SUKATANI - Apriliani, Wina Widia; Wulandari, Dyah (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Teachers have a very important role in achieving educational goals, especially in strengthening the character of students. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews and documentation. This study aims to determine the implementation of pedagogical, social and personality competencies of teachers in character formation of students of SMK Negeri 1 Sukatani. The results of this study are: 1) pedagogical competence of teachers in character formation of students at SMK Negeri 1 is carried out actively by internalizing character values in every subject and extracurricular activities, 2) social competence of teachers in character formation of students at SMK Negeri 1 is carried out by building a good school culture to create a conducive learning environment for character formation of students, 3) personality competence of teachers in character formation of students at SMK Negeri 1 is carried out by providing role models by teachers, namely providing examples of good appearance, good character and good habits.